Metabolites from Excoecaria cochinchinensis Lour. (June 2020) - Hieu, Lai Hop; Thao, Nguyen Phuong; Anh, Do Hoang; Hong Hanh, Tran Thi; Cong, Nguyen Duy; Cuong, Nguyen The; Van Thanh, Nguyen; Cuong, Nguyen Xuan; Nam, Nguyen Hoai; Quang, Ngo Dai; Van Minh, Chau
Graphical abstract: Highlights: 13 compounds including 2 new ones, were isolated from the leaves of Excoecaria cochinchinensis Lour. Compound 1 was the first rhamnofolane-type diterpenoid isolated from Excoecaria genus. Compound 9 showed strong NO production inhibitory activity with an IC50 of 6.17 ± 0.25 µM. Abstract: A new rhamnofolane-type diterpenoid (1 ) and a new phenolic derivative (2 ), together with eleven known compounds, were isolated from the leaves of E. cochinchinensis Lour. The chemical structures of these compounds were elucidated based on extensive spectroscopic analysis, including HR-QTOF-MS and NMR, and comparison with reported data. The inhibitory effects of compounds 1 –13 on lipopolysaccharide (LPS)-induced nitric oxide (NO) production in RAW264.7 cells were evaluated. As the obtained results, compound 9 showed a moderate inhibitory effects on NO production activity with an IC50 of 6.17 ± 0.25 µM, relative to that of the positive control cardamonin.